Patterns of care and outcomes for women with uterine cancer and ovarian metastases. (4th January 2019) - Jones, Nathaniel L; Huang, Yongmei; Chatterjee, Sudeshna; Tergas, Ana I; Burke, William M; Hou, June Y; Deutsch, Israel; Ananth, Cande V; Neugut, Alfred I; Hershman, Dawn L; Wright, Jason D
Abstract : Objective: For women with uterine cancer with metastases isolated to the adnexa (stage IIIA) optimal adjuvant therapy is unknown. We performed a population-based analysis to examine the use of chemotherapy, vaginal brachytherapy, and external beam therapy (in women with stage IIIA uterine cancer. Methods: The National Cancer Database was used to identify women with stage IIIA uterine cancer with ovarian metastasis from 2004 to 2012. We explored the use of chemotherapy, vaginal brachytherapy, and external beam therapy over time. Multivariable models were developed to examine factors associated with survival. Results: We identified 4088 women with uterine cancer and ovarian metastases. Overall, 56.2% of women received chemotherapy. Vaginal brachytherapy was used in 11.1%, while 36.6% received external beam therapy. Five-year survival was 64.7 % (95% CI, 62.9% to 66.5%). In a multivariable model, chemotherapy was associated with a 38% decrease in mortality (HR = 0.62; 95% CI, 0.54 to 0.71). Similarly, both external beam therapy (HR = 0.74; 95% CI, 0.65 to 0.85) and vaginal brachytherapy (HR = 0.67; 95% CI, 0.53 to 0.85) were associated with improved survival. When the cohort was limited to women who received chemotherapy, radiation was associated with improved overall survival (HR 0.74, 95% CI 0.61 to 0.90). There was no difference in survival between the use of external beam therapy and vaginal brachytherapy. Conclusions: Chemotherapy was associated with a decrease in mortality in women with endometrial cancer and ovarian metastases. The addition of radiation therapy was associated with improved overall survival, although there was no difference between external beam therapy and vaginal brachytherapy.